Lao People's Democratic Republic : Assessment Letter for the Asian Development Bank and the World Bank. (Policy Papers; Policy Paper ;, 2005)
This report provides an update of the assessment of Lao P.D.R.'s macroeconomic conditions and outlook presented at the time of the 2004 Article IV Consultation and in the Assessment Letter of March 10, 2005.